Crambe hispanica Subsp. abyssinica Diacylglycerol Acyltransferase Specificities Towards Diacylglycerols and Acyl-CoA Reveal Combinatorial Effects That Greatly Affect Enzymatic Activity and Specificity - Jeppson, Simon; Demski, Kamil; Carlsson, Anders S.; Zhu, Li-Hua; Banaś, Antoni; Stymne, Sten; Lager, Ida (Frontiers in Plant Science, 2019)
Crambe is an oil crop suitable for industrial purposes due to the high content of erucic acid (22:1) in the seed oil. The final acylation of diacylglycerols (DAG) with acyl-CoA in the production of triacylglycerols (oil) is catalysed by acyl-CoA:diacylglycerol acyltransferase (DGAT) enzymes. We identified eight forms of DGATs in crambe and characterised them in microsomal preparations of yeast expressing the enzymes using various acyl-CoAs and both di-6:0-DAG and long-chain DAG species as acyl acceptors. All DGATs accepted 22:1-CoA when using di-6:0-DAG as acyl acceptor. When di-22:1-DAG was the acyl acceptor, the DGAT1 type of enzyme utilised 22:1-CoA at a much-reduced rate compared to assays with sn-1-22:1-sn-2-18:1(oleoyl)-DAG, the most frequently available DAG precursor in crambe seeds. None of the DGAT2 enzymes was able to acylate di-22:1-DAG. Our results indicate that formation of trierucin by crambe DGATs is a limiting step for further increasing the levels of 22:1 in the previously developed transgenic crambe lines due to their poor abilities to acylate di-22:1-DAG. We also show that the acyl-CoA specificities and the enzymatic activities are highly influenced by the fatty acid composition of the DAG acyl acceptor. This finding implies that the use of artificial acyl acceptors (e.g. di-6:0-DAG) may not always reflect the actual acyl-CoA specificities of DGATs in planta. The relevance of the here reported pronounced specificities for specific DAG species exerted by DGAT enzymes is discussed in the context of the findings of DAG pools of distinct catalytic origin in triacylglycerol biosynthesis in the seed oil.